Ethical concerns relating to genetic risk scores for suicide. Issue 8 (1st September 2021) - Docherty, Anna; Kious, Brent; Brown, Teneille; Francis, Leslie; Stark, Louisa; Keeshin, Brooks; Botkin, Jeffrey; DiBlasi, Emily; Gray, Doug; Coon, Hilary
Abstract: Genome‐wide association studies (GWAS) provide valuable information in research contexts regarding genomic changes that contribute to risks for complex psychiatric conditions like major depressive disorder. GWAS results can be used to calculate polygenic risk scores (PRS) for psychiatric conditions, such as bipolar disorder or schizophrenia, as well as for other traits, such as obesity or hypertension. Private companies that provide direct‐to‐consumer (DTC) genetic testing sometimes report PRS for a variety of traits. Recently, the first well‐powered GWAS study for suicide death was published. PRS reports that claim to assess suicide risk are therefore likely to appear soon in the DTC setting. We describe ethical concerns regarding the commercial use of GWAS results related to suicide. We identify several issues that must be addressed before PRS for suicide risk is made available to the public through DTC: (a) the potential for misinterpretation of results, (b) consumers' perceptions about determinism and behavior change, (c) potential contributions to stigma, discrimination, and health disparities; and (d) ethical problems regarding the testing of children and vulnerable adults. Tests for genetic prediction of suicidality may eventually have clinical significance, but until then, the potential for individual and public harm significantly outweighs any potential benefit. Even if genetic prediction of suicidality improves significantly, information about genetic risk scores must be distributed cautiously, with genetic counseling, and with adequate safeguards.